The Epidemiology and Trend of Cancer in Jordan, 2000–2013 - Khader, Yousef S. (J Cancer Epidemiol, 2018)
OBJECTIVES: This study aimed to determine the overall incidence, trend, and epidemiology of cancer among Jordanians from 2000 to 2013 using data extracted from Jordan's Cancer Registry (JCR). METHODS: All cancer cases among Jordanians registered between 2000 and 2013 were analyzed using CanReg software and SPSS. The overall crude incidence rates (CIRs) and the age standardized rates (ASRs) of cancer per 100,000 were calculated. RESULTS: A total of 58788 cancer cases were registered during the period 2000-2013. Of those, 28545 (48.6%) were males and 30243 (51.4%) were females. About three-quarters (77.3%) of the registered patients were ≥ 40 years in age. Overall, the average crude cancer incidence rate was 82.8/100,000 population during the 14-year study period. On the other hand, the ASR was 126/100,000 during the same period (124.2 /100,000 for males and 128.4 /100,000 for females). The cumulative top cancers among males were colorectal, lung, lymphoma, urinary bladder, and prostate, respectively, while those among females were breast, colorectal, lymphoma, thyroid, and uterine. The number of cancer cases has increased from 3370 in 2000 to 5409 in 2013 (60.5% increase over the 14 years). The percentage of increase was 68.4% in females and 52.5% in males. The ASR has also increased from 113.6 per 100,000 in 2000 to 142.1 per 100.000 in 2013 with a 25.1% of increase during the 14 years. CONCLUSION: Over the 14-year study period, incidence of cancer in Jordan has increased. However, it remains lower than that in other Eastern Mediterranean and Western countries. We recommend initiating screening programs for the most common types of cancer in Jordan that have valid screening tests to detect cancer during its early stages and reduce overall morbidity and mortality.